Comparison Of The Implementation Of Pre-Court Process Before And After The Constitutional Court Decision Number: 21 / PUU-XII / 2014 In The Batang State Court - Moch. Isa Nazarudin; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The purpose of this study is to describe and analyze the basis of the court's authority to examine and decide on pretrial lawsuits, analyze and describe the legal force of pretrial decisions regarding the illegitimacy of determining criminal suspects and describe the comparative implementation of pretrial proceedings before and after the Constitutional Court ruling Number: 21 / PUU-XII / 2014 in the Batang State CourtThis research uses descriptive research type with sociological juridical and normative juridical, data collection method with literature study, observation and content analysis.At the end of the study the authors concluded that although the Constitutional Court's decision was indeed final and binding and binding and legal remedies could not be made anymore (a final decision). However, that does not mean automatically changing the Criminal Procedure Code. Because these changes can only be made by official institutions appointed by the State, namely the President and the Parliament which are the state's decision. Pre-trial objects prior to the enactment of the Constitutional Court Decision Number: 21 / PUU-XII / 2014, consisting of: whether or not a forced act of force (in the form of: arrest, detention, search and seizure); the validity of the termination of the investigation or the termination of the prosecution; and compensation or rehabilitation of pretrial objects after the entry into force of the Constitutional Court Decision Number: 21 / PUU-XII / 2014, namely the addition of a pretrial object over the validity of determining the suspect. In addition, the implications of the a quo Constitutional Court ruling also affect the validity of arrest and the validity of detention must be based on the objective requirements of the investigator; through two pieces of evidence and an examination of a prospective suspect in order to fulfill the allegation of